Natural history of the respiratory involvement in Anderson-Fabry disease - Magage, S; Lubanda, J-C; Susa, Z; Bultas, J; Karetová, D; Dobrovolný, R; Hrebícek, M; Germain, D P; Linhart, A (Journal of inherited metabolic disease, 2007)
BACKGROUND: Anderson-Fabry disease (AFD) is an X-linked disorder caused by deficient activity of enzyme alpha-galactosidase A, resulting in the accumulation of glycosphingolipids within lysosomes. Pulmonary involvement in AFD has previously been documented, but until now has been studied only in a few series of patients without any longitudinal follow-up. The aim of this study was to compare spirometric changes in AFD patients with a matched control population and to follow the subsequent progression of the disease. MATERIALS AND METHODS: Fifty individuals (27 women, 23 men, mean age 40 +/- 14 years) with AFD from 14 families underwent a static spirometric examination under standard conditions. A set of indices was compared with that of the control population. Out of this cohort, 39 individuals not receiving enzyme replacement therapy were longitudinally evaluated (median follow-up time 24 months). RESULTS: A clinically significant reduction in spirometric parameters, corresponding to mild to severe airway obstruction, was observed in 26% of women and 61% of men. During the serial follow-up, a significant (p < 0.05) age-dependent reduction of predicted %FVC and %FEV1 values was observed in male patients, while the influence of age was not seen in female patients. The %FEF(25-75) values decreased by similar degrees in men and women and in older and younger patients, indicating that progressive bronchial disease affects the small airways first. CONCLUSIONS: We have demonstrated a clinically relevant age- and sex-dependent progressive pulmonary involvement in AFD patients. The effects of enzyme replacement therapy on pulmonary involvement remain to be demonstrated.
Keywords: Sex Factors; usilovný výdechový objem; Humans; Case-Control Studies; lidé středního věku; Forced Expiratory Volume; Disease Progression; studie případů a kontrol; Respiration; Airway Obstruction; Female; mutace; dospělí; věkové faktory; Phenotype; alfa-galaktosidasa; Genotype; lidé; vitální kapacita; časové faktory; sexuální faktory; Vital Capacity; Fabryho nemoc; dýchání; Adult; Spirometry; Follow-Up Studies; ženské pohlaví; alpha-Galactosidase; stupeň závažnosti nemoci; Male; obstrukce dýchacích cest; Middle Aged; fenotyp; Genetic Predisposition to Disease; genetická predispozice k nemoci; prognóza; spirometrie; Czech Republic; Severity of Illness Index; genotyp; progrese nemoci; Age Factors; Mutation; Česká republika; mužské pohlaví; Fabry Disease; Time Factors; Prognosis; následné studie